2012
DOI: 10.1095/biolreprod.111.097345
|View full text |Cite
|
Sign up to set email alerts
|

Transient Invasive Migration in Mouse Cumulus Oocyte Complexes Induced at Ovulation by Luteinizing Hormone1

Abstract: Ovulation, the release of the oocyte from the ovarian follicle, is initiated by the luteinizing hormone surge. It is clear that highly controlled degradation of the follicle and ovarian wall is required for passage of the oocyte and accompanying cumulus cells from the follicle, but the mechanism has not yet been elucidated. Here we show that cumulus oocyte complexes (COCs) adopt transient adhesive, migratory, and matrix-invading capacities at the time of ovulation. We characterized cell adhesion, migration, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 73 publications
4
22
0
Order By: Relevance
“…Processes that are positively regulated include cellular movement, lipid metabolism, inflammatory response and immune cell trafficking. Akison et al (2012) has demonstrated that CCs in the expanded COC transition to an adhesive, motile and invasive phenotype in the periovulatory period similar to MB-231 invasive breast cancer cell line, which is in agreement with the increased cellular movement observed in CCM2 samples.…”
Section: Discussionsupporting
confidence: 76%
“…Processes that are positively regulated include cellular movement, lipid metabolism, inflammatory response and immune cell trafficking. Akison et al (2012) has demonstrated that CCs in the expanded COC transition to an adhesive, motile and invasive phenotype in the periovulatory period similar to MB-231 invasive breast cancer cell line, which is in agreement with the increased cellular movement observed in CCM2 samples.…”
Section: Discussionsupporting
confidence: 76%
“…However, currently, we cannot exclude the possibility that the inhibitory effect of both miR‐125a‐3p and Fyn siRNA on ovulation is not confined to mural granulosa cells. In that context, several studies pointed out the importance of migration of the cumulus cells in the process of cumulus expansion (37, 38). Because cumulus expansion is required for adequate ovulation (39), it is possible that over‐expression of miR‐125a‐3p and down‐regulation of Fyn may have interfered with cumulus migration, hampering its expansion and, hence, contributing to the inhibitory effect of miR‐125a‐3p and Fyn siRNA on ovulation in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Betaglycan is a repressor of cell motility, and its down-regulation promotes motility in metastatic cancers (43). We recently reported that cumulus cells selectively acquire invasive motility during the periovulatory window (44) and this down-regulation of Betaglycan would be expected to facilitate this acquisition of motility in ovulating COC. Heparin treatment of COCs significantly increased Betaglycan expression which was reversed by GDF9 co-treatment providing the first evidence that Betaglycan mRNA is repressed in COC and this is GDF9 dependent.…”
Section: Discussionmentioning
confidence: 99%